Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Performance evaluation of a newly developed portable FAIMS instrument for atmospheric trace gas detection - Katsuya Ujimoto; Kunihiro Tan; Yoshihiko Miki; Akira Sugawa; Atsuo Hashimoto; Tomoki Nakayama (Journal of Environmental Management, 2025)

Chemical constituents and aldose reductase inhibitory activities of Betula alba bark and leaves - Tomoki Iguchi; Minpei Kuroda; Nanami Akiyama; Mariko Hashimoto; Yoshihiro Mimaki (Natural Product Research, 2022)

Endovascular Biopsy: In Vivo Cerebral Aneurysm Endothelial Cell Sampling and Gene Expression Analysis - Daniel L. Cooke; David B. McCoy; Van V. Halbach; Steven W. Hetts; Matthew R. Amans; Christopher F. Dowd; Randall T. Higashida; Devon Lawson; Jeffrey Nelson; Chih-Yang Wang; Helen Kim; Zena Werb; et al. (Translational Stroke Research, 2018)

Translational Research Using a Mouse Model of Intracranial Aneurysm - Kosuke Wada; Hiroshi Makino; Kenji Shimada; Fumiaki Shikata; Atsushi Kuwabara; Tomoki Hashimoto (Translational Stroke Research, 2014)

Evaluation of three phytoplankton species as food for the pearl oyster Pinctada fucata - Tomoki Hashimoto; Katsuya Hyodoh; Takuma Hirose; Satoshi Nishikawa; Toshiya Katano; Shin-ichi Nakano (Aquaculture International, 2008)

Effect of CYP2D6*10 on pharmacokinetic variability of routinely administered metoprolol in middle-aged and elderly Japanese patients - Masato Taguchi; Takashi Nozawa; Tomoki Kameyama; Hiroshi Inoue; Chihiro Takesono; Akiko Mizukami; Yukiya Hashimoto (European Journal of Clinical Pharmacology, 2003)

Induction of focal angiogenesis through adenoviral vector mediated vascular endothelial cell growth factor gene transfer in the mature mouse brain - Guo-Yuan Yang; Bin Xu; Tomoki Hashimoto; Madeleine Huey; Thomas Chaly; Rong Wen; William L. Young (Angiogenesis, 2003)